Planned mode of birth after previous cesarean section: A structured review of the evidence on the associated outcomes for women and their children in high-income setting - Fitzpatrick, Kathryn E.; Quigley, Maria A.; Kurinczuk, Jennifer J. (Frontiers in Medicine, 2022)
We have updated our abstract following the helpful reviewer comments, as shown in the revised version of the manuscript uploaded. However, the abstract is now 27 words over the 350-word limit. Please let us know if you need us to cut this down.